2014
DOI: 10.1177/1477370814551211
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between criminology studies and punitive attitudes

Abstract: Policymakers and researchers have long been interested in the punitive attitudes of police and correctional officers. This research examined the punitive attitudes of 206 police and correctional officers at the beginning and towards the end of academic studies. The results indicate that (a) the police officers held more punitive attitudes compared with the correctional officers; (b) the correctional officers, but not the police officers, held less punitive attitudes in the last year than in the first year of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 63 publications
2
27
1
2
Order By: Relevance
“…The way people perceive and think about crime and punishment is a central aspect of normative culture and formal social control (Adriaenssen & Aertsen, 2015;Stylianou, 2003). In recent decades, the public's attitudes to crime, punishment, and its alternatives have become an important area of criminological research (Chen & Einat, 2015;Kutateladze & Crossman, 2009;Payne et al, 2004Payne et al, , 2010. Policies on crime and justice are often shaped by policymakers' perceptions of public opinion (Indermaur et al, 2012).…”
Section: The Public's Attitudes and Justice Policiesmentioning
confidence: 99%
“…The way people perceive and think about crime and punishment is a central aspect of normative culture and formal social control (Adriaenssen & Aertsen, 2015;Stylianou, 2003). In recent decades, the public's attitudes to crime, punishment, and its alternatives have become an important area of criminological research (Chen & Einat, 2015;Kutateladze & Crossman, 2009;Payne et al, 2004Payne et al, , 2010. Policies on crime and justice are often shaped by policymakers' perceptions of public opinion (Indermaur et al, 2012).…”
Section: The Public's Attitudes and Justice Policiesmentioning
confidence: 99%
“…Hough and Moxon, 1985), while others found no association between age and punitive attitudes (e.g. Chen and Einat, 2015;Shafiq et al, 2016). The same situation occurs with educational experience: although some studies have shown a correlation between higher academic status and a decline in the level of punitive attitudes (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…It appears that men prefer more punitive attitudes compared to women, and (of interest to the current study) this was especially true in Norway and Sweden compared to the other Scandinavian countries (Bondeson, 2005). Such demographical differences have also been reported internationally (Chen & Einat, 2015). Bondeson (2005) found that people with low educational attainment also have a more punitive view of criminal justice sanctions.…”
Section: Factors Influencing Attitudes and Judgements: Individual Difmentioning
confidence: 64%